Resistance of Moroccan lentil genotypes to Orobanche crenata infestation. Issue 3 (4th May 2019) - Mbasani-Mansi, Joseph; Briache, Fatima Zahra; Ennami, Mounia; Gaboun, Fatima; Benbrahim, Nadia; Triqui, Zine El Abidine; Mentag, Rachid
ABSTRACT: Lentil ( Lens culinaris Medik.) is one of the legume crops greatly affected by Orobanche crenata parasitism in the Mediterranean region. Losses caused can reach 100%. Development of resistant cultivars remains the most promising way to reduce Orobanche damage. Our objective was to assess the resistance levels of 17 Moroccan lentil cultivars to this parasitic weed through field, pot, and Petri dish evaluations. Field results revealed large variation for Orobanche infestation levels among assessed genotypes; emerged orobanche spikes ranged from 0.09 to 0.70 per host plant. In pot and Petri dish experiments, number of Orobanche infestation events (OIE) varied from 1.25 to 7 and from 3 to 26, respectively. Principal components analysis (PCA) based on infestation parameters recorded in all trials indicated that the first two components explained 79.7% of the total variance observed and suggested that severity examined in the field could be a suitable selection criterion for resistance to O. crenata . LR9 and V02 were found to be the most resistant genotypes, whereas V08 was the most susceptible one. Lentil defense mechanisms included: i) reduction in host root biomass, ii) reduction in O. crenata attachment on host roots, and iii) delayed development of OIE. LR9 and V02 were promising genotypes for deployment in a lentil breeding program for developing cultivars with resistance to O. crenata .